Transcriptional Control of Dual Transporters Involved in α-Ketoglutarate Utilization Reveals Their Distinct Roles in Uropathogenic Escherichia coli - Cai, Wentong; Cai, Xuwang; Yang, Yongwu; Yan, Shigan; Zhang, Haibin (Frontiers in Microbiology, 2017)
Uropathogenic Escherichia coli (UPEC) are the primary causative agents of urinary tract infections. Some UPEC isolates are able to infect renal proximal tubule cells, and can potentially cause pyelonephritis. We have previously shown that to fulfill their physiological roles renal proximal tubule cells accumulate high concentrations of α-ketoglutarate (KG) and that gene cluster c5032-c5039 contribute to anaerobic utilization of KG by UPEC str. CFT073, thereby promoting its in vivo fitness. Given the importance of utilizing KG for UPEC, this study is designed to investigate the roles of two transporters KgtP and C5038 in KG utilization, their transcriptional regulation, and their contributions to UPEC fitness in vivo. Our phylogenetic analyses support that kgtP is a widely conserved locus in commensal and pathogenic E. coli, while UPEC-associated c5038 was acquired through horizontal gene transfer. Global anaerobic transcriptional regulators FNR and ArcA induced c5038 expression in anaerobiosis, and C5038 played a major role in anaerobic growth on KG. KgtP was required for aerobic growth on KG, and its expression was repressed by FNR and ArcA under anaerobic conditions. Analyses of FNR and ArcA binding sites and results of EMS assays suggest that FNR and ArcA likely inhibit kgtP expression through binding to the -35 region of kgtP promoter and occluding the occupacy of RNA polymerases. Gene c5038 can be specifically induced by KG, whereas the expression of kgtP does not respond to KG, yet can be stimulated during growth on glycerol. In addition, c5038 and kgtP expression were further shown to be controlled by different alternative sigma factors RpoN and RpoS, respectively. Furthermore, dual-strain competition assays in a murine model showed that c5038 mutant but not kgtP mutant was outcompeted by the wildtype strain during the colonization of murine bladders and kidneys, highlighting the importance of C5038 under in vivo conditions. Therefore, different transcriptional regulation led to distinct roles played by C5038 and KgtP in KG utilization and fitness in vivo. This study thus potentially expanded our understanding of UPEC pathobiology.